A sea of birds: first bird population assessments in the Saudi Arabian Red Sea - Licia Calabrese; Julie Ann Riordan; Imogen Anne Lloyd; Alexa Darby Foster; Thomas Edward Collier; Johannes Alexandre Chambon; Yasir Wusayl Aljohani; Essa Ali Alhamdi; Patrick Rowan Beaumont; Ivor Douglas Williams; Omar Al-Attas (Frontiers in Marine Science, 2024)
Introduction Seabirds and other insular birds are an important part of marine ecosystems and are increasingly threatened worldwide. Phenology, abundance, distribution, and breeding success are important baseline parameters needed to evaluate population trends and dynamics, identify biodiversity hotspots and potential breeding sites, and assess habitat selection. In the Red Sea basin, reliable and complete data on birds are lacking for islands in most of the Important Bird Areas (IBA). Such data are now especially important since development projects have started at several of these locations. Here, we assess the distribution, abundance, phenology, and population trends of 13 bird species that breed in the Duba Islands, Al Wajh Bank, and Al Lith Islands. Breeding success and habitat selection for six species were also assessed. Methods Between December 2020 and August 2023, more than 90 islands were visited multiple times with different frequencies. All nests were counted, and the area occupied by the different colonies was georeferenced. Breeding success was assessed by visiting selected colonies multiple times until the chicks were ready to fledge. Habitat selection was determined by analyzing the habitat found in the georeferenced colonies. Results More than 25,000 nests were counted each year, mainly in the summer, on more than 75 islands. Of the 13 species studied, the most abundant and widespread species was the White-cheeked tern, and the second most widespread was the Osprey. Discussion We estimate that the Al Wajh Bank hosts the following percentages of global breeding populations: Crab plover: 5%, Sooty gull: 17%–35%, White-eyed gull: 15%, Bridled tern: 1%, White-cheeked tern: 4%, and Lesser crested tern: 2%, making the area a regional and global hotspot for these species. Some of the islands occupied by breeding birds are slated for development for tourism activities as part of the Kingdom’s tourism expansion plans. At the same time, there are several ambitious conservation programs underway in these areas. To be effective, such programs require reliable and comprehensive data of the kind presented here.